Dzikir As Cognitive Reprogramming: Transforming Internalized Negative Beliefs among Muslim Students - Nadhif, Moh.; Sirojuddin, Akhmad; Bakhiet, Bakri Muhammad; Acetylena, Sita; Ma'arif, Samsul (Interdisciplinary Journal of Social Sciences, 2026)
This study examines the role of dzikir as a cognitive reprogramming intervention in transforming internalized negative beliefs among Muslim students. Rooted in the intersection of Islamic education, cognitive psychology, and emerging neuro-religious perspectives, the study addresses how repetitive parental narratives such as “life is difficult” or “earning money is hard” contribute to the formation of maladaptive cognitive schemas and scarcity-oriented mindsets. Despite the growing body of research on cognitive restructuring, the integration of Islamic spiritual practices into contemporary psychological frameworks remains limited. This study employs a convergent mixed-methods design, combining quantitative and qualitative approaches. Quantitative data were collected through a quasi-experimental pre-test–post-test design involving 80 participants and analyzed using paired sample t-tests and effect size analysis. Qualitative data were obtained from semi-structured interviews with 20 participants and analyzed using thematic analysis to explore participants’ lived experiences and cognitive transformation processes. The findings reveal statistically significant improvements in cognitive belief orientation, including a reduction in scarcity mindset and an increase in positive life orientation and self-efficacy (p < .001). Effect size analysis indicates a strong practical impact of the intervention. Qualitative findings further highlight three key themes: internalized negative narratives, emergence of cognitive awareness, and the transformative role of dzikir in reshaping internal dialogue and emotional states. These results suggest that structured and meaning-oriented dzikir practices can serve as an effective culturally grounded approach to cognitive restructuring. While the study does not directly measure neural activity, the findings provide indirect evidence of possible neurocognitive adaptation associated with repetitive spiritual practices. This study contributes to the development of a Neuro-Religious Cognitive Reprogramming Framework, bridging Islamic spiritual praxis and cognitive science. The findings also offer practical implications for integrating dzikir-based interventions into Islamic education and counseling to promote healthier cognitive patterns and improved psychological well-being.